LOBI DAN NEGOSISASI PADA HARIAN PAGI METRO RIAU DALAM MEMPERTAHANKAN PENGIKLAN - Ikhsan Nofriansyah; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Daily Morning Metro Riau meerupakan one of the local print media are engaged in the business of economic news. One phenomenon that appears on this medium is the large number of incoming advertising in the Daily Morning Metro Riau, while on the reader's interest is still not comparable to reading other print media such as Riau POS . This research aims to : ( 1 ) How does the process of lobbying and carried negosias Daily Morning Metro Riau preformance retain advertisers. ( 2 ) How lobbying and negotiation techniques used Daily Morning Metro Riau in maintaining advertisers. ( 3 ) What factors affect advertisers in choosing Daily PagiMetro Riau as a media product or service . This uses a descriptive analysis with a qualitative approach, which menekannkan in perspective , assessment or emotional expression from informants were surveyed regarding the problems examined are categorized as data. The data source consists of primary data is data obtained from the Daily Morning Metro Riau as supporting this research . That where the data will be processed researchers to develop what is presented by the researcher . Secondary data is data that is sourced from the Daily Morning Metro Riau documentation in the form of a general overview , ornaisasi structure , as well as the tasks and roles karyawan.Pengumpulan data using observations ( interview) , interviews , and analysis of data in dokumentasi.Teknik of the research is the presentation of data analysis techniques , and withdrawal as well as the testing of data validity checking techniques kesimpulan.Sedangkan through the extension of participation and triangulation . The results showed that ( 1 ) The process of lobbying and negotiations are conducted Daily Morning Metro Riau run through four stages where ad management Daily Morning Metro Riau instrumental in channeling strategy of lobbying and negotiations with advertisers . ( 2 ) Engineering lobbying and negotiations are conducted Daily Morning Metro Riau has each of the two stages in which the technique lobby conditioning approach . This approach focuses on lobbying efforts to build new habits and networking approach where this approach seek relationships as much as possible in advance , and not oriented on the outcome while negotiating techniques exist to make the agenda and make the deadline . And ( 3 ) Factors affecting advertisers choose Daily Morning Metro Riau because ads on Metro Morning Daily Riau always varied and innovative , because the design of the resulting image has been very helpful in changing the mindset of audiences Key Word : Loby, Negotiation, News paper